'Integration' or 'Selective Incorporation'? The Modes of Governance in Informal Trading Policy in the Inner City of Johannesburg. Issue 4 (2nd April 2016) - Pezzano, Antonio
Abstract: This article explores the modes of governance in informal trading policy in the inner city of Johannesburg. It highlights the different and contradictory empirical models of informal trading management which result from the interaction of multiple and plural local actors on the ground and the different strategies employed by informal traders in engaging the state. The article argues that Johannesburg municipal authorities exert a contradictory double agenda instead of governing the complexity of informality. The result is asymmetric governance functional to a neoliberalisation of the urban policies which produces a selective incorporation of informal traders from above and from below.